Ways of thinking senior high school student to solve geometri van hiele problem use reversible thinking ability - Pebrianti, Aneu; Suhendra, Suhendra (Al-Jabar: Jurnal Pendidikan Matematika, 2023)
Background: Reversible thinking is a cognitive strategy that involves tracing the path from an end result back to the starting point. It is particularly useful in problem-solving.Aim: This study aims to describe the thought process of high school students in finding solutions to van hiele geometry problems using reversible thinking ability.Method: A case study approach was employed. The participants were two high school students, and the research tools included written tests and interviews. These instruments were used to delve into the students' written responses.Result: The findings revealed two key aspects: firstly, the students' van Hiele geometry thinking was predominantly at the deduction stage, evidenced by their ability to model geometric shapes based on their characteristics. Secondly, their reversible thinking in geometry was demonstrated through the simplification of fractional operations to obtain whole parts.Conclusion: The study highlights the efficacy of reversible thinking in solving geometric problems and provides insights into the cognitive processes of high school students. The ability to reverse engineer solutions from a known outcome back to the starting conditions is a valuable skill in mathematical problem-solving.